Memos from a theatre lab : immersive theatre & time - Dinesh, Nandita (Series in performing arts., 2018)
Drawing from Dinesh's findings in Memos from a Theatre Lab: Exploring What Immersive Theatre "Does" and Memos from a Theatre Lab: Spaces, Relationships, & Immersive Theatre, this practice-based-research project, the third in a series of Immersive Theatre experiments in Dinesh's theatre laboratory, considers the impact of duration when using immersive theatrical aesthetics toward educational and/or socio-political objectives. Dinesh frames the third experiment in her New Mexican theatre laboratory by placing its data and analyses in conversation with Information for/from Outsiders: Chronicles from Kashmir: a twenty-four hour long immersive, theatrical experience that Dinesh has been developing with Kashmiri theatre artists since 2013. In doing so, Dinesh seeks to create 'conceptual bridges' between practice and theory; between her experiments in New Mexico and the work that she does in Kashmir; between the generation of frameworks to develop Dinesh's own repertoire as a practitioner-researcher, and the creation of shareable strategies that might be used by other Immersive Theatre scholars, artists, and students.